2014
DOI: 10.1021/mp5000899
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic-Targeted Gene Delivery Using Cationic Mannan Vehicle

Abstract: The incidence of hepatic diseases continuously increases worldwide and causes significant mortality because of inefficient pharmacotherapy. Gene therapy is a new strategy in the treatment of hepatic diseases, but the disadvantages of insufficient retention in the liver and undesirable side effects hinder its application. In this study, we developed a novel nonviral vehicle targeted to liver. Mannan was cationized with spermine at varying grafted ratios to deliver the gene and was optimized in cytotoxicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…To conjugate [ 18 F]­BCN or [ 19 F]­BCN to mannan, the molecular structure of mannan needs to be functionalized with tetrazine moieties. In literature, strategies for activation of mannan include periodate oxidation, cyanylation and carbamoylation. In periodate oxidation reactions, part of the hexasaccharide rings is opened to form aldehydes, and new epitopes may be generated in the resulted conjugates . Cyanylation or carbamoylation activate some of the hydroxyl groups without breaking the sugar ring structures.…”
mentioning
confidence: 99%
“…To conjugate [ 18 F]­BCN or [ 19 F]­BCN to mannan, the molecular structure of mannan needs to be functionalized with tetrazine moieties. In literature, strategies for activation of mannan include periodate oxidation, cyanylation and carbamoylation. In periodate oxidation reactions, part of the hexasaccharide rings is opened to form aldehydes, and new epitopes may be generated in the resulted conjugates . Cyanylation or carbamoylation activate some of the hydroxyl groups without breaking the sugar ring structures.…”
mentioning
confidence: 99%
“…Mannose was activated by N,N′-Dicyclohexylcarbodiimide followed by their conjugation with spermine. However, in vivo evaluation of complexes revealed that cationic character of conjugates overshadowed the targeting efficacies of glycans [64].…”
Section: Nonparenchymal Cell Targetingmentioning
confidence: 99%